Monogenic glucokinase diabetes and pregnancy: a case study - Haladová, Iva; Čechurová, Daniela; Lacigová, Silvie; Rušavý, Zdeněk (Wiener klinische Wochenschrift, 2015)
It is estimated that up to 3 % of patients with gestational diabetes have glucokinase diabetes, termed also maturity-onset diabetes of the young type 2. The disorder has autosomal dominant inheritance. There is a 50 % risk of transmission of the gene to next generation. Two scenarios with different approach to the treatment may occur in pregnancy with glucokinase diabetes: either the fetus inherits the glucokinase mutation and the treatment of maternal hyperglycemia by insulin could increase the risk of fetal growth restriction, or the fetus is without glucokinase gene mutation and untreated hyperglycemia of the mother increases the risk of macrosomia and perinatal morbidity and insulin therapy is necessary. This article describes the outcome of two pregnancies in a patient with monogenic diabetes with glucokinase deficiency. A specific approach to the treatment is discussed.
Keywords: těhotenství; výsledek těhotenství; Humans; Diabetes Mellitus, Type 2; lidé; inzulin; hypoglykemika; Treatment Outcome; Insulin; diabetes mellitus 2. typu; Female; Male; Adult; výsledek terapie; mužské pohlaví; gestační diabetes; Pregnancy Outcome; ženské pohlaví; Hypoglycemic Agents; Diabetes, Gestational; dospělí; Pregnancy